Tradition and science of Trataka kriya: A comprehensive review - Palash Pramanik; Sridip Chatterjee (Yoga-Mimamsa)
Trataka kriya (TK) is one of the leading practices of the six cleansing techniques (shatkarma) of Hathayaga. It involves steady gazing at a small point until tears come out. The objectives of this review are to systematically collect the traditional references of TK and analyze the latest scientific evidences that highlight its immediate- and long-term physiological and therapeutic effects. To fulfill the purpose of the study, a rigorous advanced search was conducted in June 2024 in PubMed, Scopus, and Web of Science. In addition, Yoga Mimamsa, a peer-reviewed journal, was searched manually to obtain the related literature. Randomized controlled trials, pre-post study designs, self-as-control studies, and repeated measures studies published in the English language from January 2000 to May 2024, using trataka as the intervention, were considered in this study. Then, we extracted the data from each study into a standardized population, intervention, comparison, outcomes, and study table. Using the PRISMA guidelines, 16 studies were included in this review based on inclusion criteria. Of these, nine studies were predominantly on the general healthy population, and the remaining seven studies were on patients with ophthalmic disorders. However, TK is found beneficial in improving cognitive performance, heart rhythm, emotional control, and mental relaxation. It is also effective for eye health. The therapeutic values of the TK have not yet been scientifically investigated to the fullest extent. For further progress, substantial research is needed to validate the findings and to ascertain the long-term effects of trataka on health and disease.